Aplikasi Hadisku Sebagai Media Penyebaran Hadis Era Revolusi 5.0 - Syahidil Mubarik Mh Syahid; Ekatul Hilwatis Sakinah (Al-Mu'tabar, 2023)
The development of technology in the era of revolution 5.0, especially application-based information technology, has made hadith studies also experience its development. Hadith is now available in digital form and can be enjoyed by all groups. This paper aims to find out the use of Play Store as a media for disseminating hadith with a focus on the Hadith My application. The method used in this research is qualitative descriptive analytics with library research. The results show that the role of Google Play Store as a media for the dissemination of hadith can be seen from the number of hadith applications available on the platform. Specifically, there are three trends in the hadith applications contained in the Play Store namely; hadith applications based on hadith books, hadith themes, and those presented in general including those that combine the two. Furthermore, this paper presents HadisKu application as one example of a hadith application in the Play Store. This application, which provides hadith sourced from 14 Imams, is comprehensive as can be seen from the menu features such as hadith collection, hadith status, hadith sanad sequence, description of narrators, knowledge about hadith, and biographies of hadith Imams. This application even presents daily selected hadith and daily Islamic readings that can be used by users as a means of daily reading. The existence of this application has benefited users in facilitating the study of hadith. In addition, the system in this application can also be used as a new example for developers of other hadith applications.